2008
DOI: 10.2106/jbjs.f.00628
|View full text |Cite
|
Sign up to set email alerts
|

The Rationale for Tilt-Adjusted Acetabular Cup Navigation

Abstract: For navigation systems that rely on the pelvic anterior plane, cup alignment values can be converted to familiar target values with our nomogram with good accuracy and reproducibility. The next generation of navigation systems should be able to measure the pelvic tilt for each individual patient and automatically adjust alignment values.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
236
0
11

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 242 publications
(264 citation statements)
references
References 22 publications
17
236
0
11
Order By: Relevance
“…Lembeck et al, in their cohort, observed a range of supine pelvic tilt from À17°to 3°, and standing pelvic tilt ranged from À27°to 3° [32]. Patients with hip disorders similarly have a wide range of individual pelvic tilt measurements [10], ranging greater than 60°in one study [39]. We (1) asked if acetabular anteversion measurements using the femoral head centers differed from those using the posterior ischia and (2) sought to understand the effects of changing obliquity, rotation, and tilt of a pelvis in a CT scanner on the measurement of acetabular variables.…”
Section: Discussionmentioning
confidence: 90%
“…Lembeck et al, in their cohort, observed a range of supine pelvic tilt from À17°to 3°, and standing pelvic tilt ranged from À27°to 3° [32]. Patients with hip disorders similarly have a wide range of individual pelvic tilt measurements [10], ranging greater than 60°in one study [39]. We (1) asked if acetabular anteversion measurements using the femoral head centers differed from those using the posterior ischia and (2) sought to understand the effects of changing obliquity, rotation, and tilt of a pelvis in a CT scanner on the measurement of acetabular variables.…”
Section: Discussionmentioning
confidence: 90%
“…A rough estimation of pelvic rotation on AP radiographs may be done using the Tönnis' foramen obturator index [29,30]. By approximation, pelvic tilt may be assessed by e. g. the coccygeal-symphysis index on AP radiographs [24], but for exact angular information lateral radiographs of the pelvis are necessary [22]. A second limitation is our experimental setup.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to the definition of Babisch [22], pelvic tilt was defined as the angle between the vertical functional coronary plane (FCP) and the anterior pelvis plane (APP) (▶ Fig. 2).…”
Section: Experiments For Pelvic Tiltmentioning
confidence: 99%
See 2 more Smart Citations